COMPARATIVE PHARMACEUTICO-ANALYTICAL STUDY OF GANGADHA KWATH, GHANAVATI WITH SPECIAL REFFRENCE TO ITS ANTI-BACTERIAL ACTIVITY (International Journal of Food and Nutritional Sciences, 2022)
One of the main strategies in Ayurvedic medicine is to increase bodys natural resistance to the disease. Ayurveda is being practiced since ancient times as an important speciality aiming at rejuvenation and geriatric care. It is considered to be one of the oldest of healthcare systems, and is based on sound scientific principles. It literally means the Science of Life. It is not just a medicinal system, but also a way of life. Ayurveda deals with the physical, as well as spiritual health. Ayurvedic compound formulations too have reached extensive acceptability as therapeutic agents for several diseases. Ayurveda is attracting modern scientists in finding out solutions for many challenging diseases.